Adesão de microrganismo sobre superfície de cerâmica de dissilicato de lítio exposta a diferentes soluções - Monteiro, Beatriz Cristiane Zuin [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Cervical length and the influence of some solutions is a concern in relation to ceramic restorations. It is known that to obtain success and longevity with esthetic restorations it is essential to have periodontal health. Cervical endings that are located subgingivally can cause damage to it. In addition, some solutions commonly used can affect the properties of some restorative materials. However, the literature is sparse when it comes to the influence of such solutions in dental ceramics. The increase in surface roughness caused by these may facilitate adherence of some pathogens, causing gum inflammation. Thus, the present study evaluated the influence of different solutions on the surface roughness of ceramic lithium disilicate and adhesion of microorganism that is involved in the pathogenesis of periodontal disease (Fusobacterium nucleatum). 54 cylindrical ceramic samples of lithium disilicate (5x1mm) were prepared. The samples were randomly distributed into groups according to which the solutions were immersed: sodium fluoride 0,2%, acidulated phosphate fluoride 1,23%, artificial saliva, cola, buccal mouthwash and hydrogen peroxide 7,5%. The roughness readings were performed at the beginning and after the immersion process. After soaking the microbiological testing was performed. For this, the organism was grown on BHI agar plus defibrinated horse blood. After standardization of the inoculum, the species was inoculated into BHI broth with the sample inside. After 72 hours, it was removed, rinsed in a saline with a tube for detachment of adhered cells. These samples were then serially diluted and plated to assess the amount of adhered cells, by counting the colony forming units. As a result, it can be seen that after the period of immersion in the solutions, there was a statistically significant increase for all...

A extensão cervical e a influência de algumas soluções é uma preocupação em relação às restaurações cerâmicas. Sabe-se que para se obter sucesso e longevidade com restaurações estéticas é imprescindível que se tenha saúde periodontal. Términos cervicais que se localizam subgengivalmente podem causar danos a este. Além disso, algumas soluções usualmente utilizadas podem afetar as propriedades de alguns materiais restauradores. Porém, a literatura é escassa quando se trata da influência de tais soluções nas cerâmicas odontológicas. O aumento da rugosidade de superfície causada por estas pode facilitar a adesão de alguns microrganismos patogênicos, provocando inflamação gengival. Sendo assim, o presente estudo avaliou a influência de diferentes soluções na rugosidade de superfície de cerâmica de dissilicato de lítio e a adesão de microrganismo que está envolvido na patogênese da doença periodontal (Fusobacterium nucleatum). Foram confeccionados 54 corpos-de-prova cilíndricos de cerâmicas de dissilicato de lítio (5 x 1 mm). Os corpos-de-prova foram distribuídos aleatoriamente em seis grupos, de acordo com as soluções em que foram imersas: fluoreto de sódio a 0,2%, fluoreto fosfatado acidulado à 1,23%, saliva artificial, refrigerante de cola, colutório bucal e peróxido de hidrôgenio a 7,5%. As leituras de rugosidade foram realizadas no período inicial e após o processo de imersão. Após imersão foi realizado os ensaios microbiológicos. Para este, o microrganismo foi cultivado em ágar BHI acrescido de sangue desfibrinado de cavalo. Após a padronização do inócuo, a espécie foi inoculada em caldo BHI com o corpo-de-prova dentro. Após 72 horas, esta foi removida, lavada em um tubo com solução fisiológica para desprendimentos das células aderidas. Esses corpos-de-prova sofreram diluições...
Keywords: Aspereza de superfície; Fusobacterium nucleatum; Cerâmicas odontológicas; Doenças periodontais; Surface roughness